Representasi Nasionalisme dalam Lagu Korea Selatan “Dokdoneun Urittang” (Dokdo adalah Tanah Kami) Versi Tahun 2017 - Nikki Vernishia, Ni Putu Anasthasia; Sugiarica Joni, I Dewa Ayu; Pradipta, Ade Devia (E-Jurnal Medium, 2021)
Songs are universal media that effectively convey messages to a wide audience. “Dokdoneun Urittang” or Dokdo is our land is one of the South Korean songs which is not only entertaining but contains a message of nationalism in it. This research is descriptive-qualitative with the semiotic approach of Ferdinand de Saussure. This study aims to explain the representation of nationalism contained in the “Dokdoneun Urittang”. The results of this study indicate that the nationalism seen in the song is nationalism which has general principles of unity, liberty and identity.   Keywords : Representation, nationalism, South Korea